Croatian Short Story and Antun Gustav Matoš - Sablić Tomić, Helena (Poznańskie Studia Slawistyczne, 2014)
Antun Gustav Matoš has affirmed the Croatian short story and that is why his short story collections have initiated a major „breakthrough” in terms of this genre’s reception. His narrative oeuvre includes the following collections: Iverje (Wood Shavings, 1899), Novo iverje (New Wood Shavings, 1900) and Umorne priče (Tired Tales, 1909). Depending on the type of motif, his short stories have been read as follows: 1. stories about local people and events; 2. humorous stories about people at home and abroad; 3. stories about unusual, unbelievable „unreal” events; 4. stories of enchanting and yearning love; 5. lyrical cadenzas. His symbolic-grotesque-fantastic story Moć savjesti (The Power of Conscience) marked his entry into the world of narrative literature. In this story, the binary relationship between the theme and the motif is recognised in the gap between the world of wakefulness and the world of dreams, reality and fantasy, what is real and what is unreal, the actual life and the ideal life, the object and the subject. At the same time, however, Matoš is trying to unite these opposites. In his other short stories, unusual plots become an expression of a deep ontological crisis which engulfed the European culture and art during modernism. The maxim of modern art at the turn of the century is „the world is a text”: art is a subjective reconstruction of the world and therefore plots, with all their logical cause and effect relationships, are no longer important since they cannot express other spheres of consciousness. In his short stories, the bizarre plots were used by Matoš to join two worlds, the world of outward reality and the world of imagination, the empirical and the fantastic, the possible and the impossible.